ChemInform Abstract: Hydrothermal Synthesis of a Ba and Mg Co‐Doped Bi12GeO20 Photocatalyst with Enhanced Visible Light Catalytic Activity. Issue 18 (April 2016) - Chen, Yi; Fang, Jianzhang; Lu, Shaoyou; Cen, Chaoping; Cheng, Cong; Ren, Lu; Feng, Weihua; Fang, Zhanqiang
Abstract: (1% Ba, Mg) co‐doped Bi12 GeO20 is prepared by hydrothermal reaction of stoichiometric amounts of Bi(NO3 )3, GeO2, Ba(NO3 )2, and Mg(NO3 )2 in alkaline (5M NaOH) solution (autoclave, 180 °C, 12 h).